Editorial - Pacheco, Ana Paula; Silva, Anderson Gonçalves da; Fonseca, Maria Augusta (Literatura e Sociedade, 2023)
Editorial por Ana Paula Pacheco, Anderson Gonçalves da Silva, Maria Augusta Fonseca.